2019
DOI: 10.3389/fnagi.2019.00261
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Differences in Physical Exercise-Mediated Cognitive Recovery Following Middle Cerebral Artery Occlusion in Aged Rats

Abstract: Stroke remains a leading cause of death and disability in the United States. No current treatments exist to promote cognitive recovery in survivors of stroke. A previous study from our laboratory determined that an acute bout of forced treadmill exercise was able to promote cognitive recovery in 3 month old male rats after middle cerebral artery occlusion (MCAo). In this study, we tested the hypothesis that 6 days of intense acute bout of forced treadmill exercise (physical exercise – PE) promotes cognitive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It was suggested that the effect of WBV in rats may be mediated via the reduction of hippocampal neuronal degeneration and by improving expression of synaptic proteins ( Cariati et al, 2021 ; Peng et al, 2021 ). Post-stroke high-intensity interval training reduced ischemic brain damage and upregulated pTrkB (a major cascade of BDNF actions) and FNDC5 expression in the cortex of rats ( Pin-Barre et al, 2021 ), which underscores its role in neuronal survival, hippocampal neurogenesis, synaptic plasticity, and functional recovery ( Liu and Nusslock, 2018 ; Cohan et al, 2019 ; Luo et al, 2019 ). Therefore, future studies investigating the efficacy of post-stroke irisin treatment to improve mitochondrial and vascular functions, thus protecting the brain from ischemic damage and improving cognition, are needed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It was suggested that the effect of WBV in rats may be mediated via the reduction of hippocampal neuronal degeneration and by improving expression of synaptic proteins ( Cariati et al, 2021 ; Peng et al, 2021 ). Post-stroke high-intensity interval training reduced ischemic brain damage and upregulated pTrkB (a major cascade of BDNF actions) and FNDC5 expression in the cortex of rats ( Pin-Barre et al, 2021 ), which underscores its role in neuronal survival, hippocampal neurogenesis, synaptic plasticity, and functional recovery ( Liu and Nusslock, 2018 ; Cohan et al, 2019 ; Luo et al, 2019 ). Therefore, future studies investigating the efficacy of post-stroke irisin treatment to improve mitochondrial and vascular functions, thus protecting the brain from ischemic damage and improving cognition, are needed.…”
Section: Discussionmentioning
confidence: 96%
“…Irisin treatment reduces brain infarct volume, neurological deficit scores, and neuronal injuries in mice subjected to MCAO (Asadi et al, 2018). Post-stroke high-intensity interval training reduced ischemic brain damage and upregulated pTrkB (a major cascade of BDNF actions) and FNDC5 expression in the cortex of rats (Pin-Barre et al, 2021), which underscores its role in neuronal survival, hippocampal neurogenesis, synaptic plasticity, and functional recovery (Liu and Nusslock, 2018;Cohan et al, 2019;Luo et al, 2019). Irisin treatments have also demonstrated improved memory and synaptic plasticity in mouse models of Alzheimer's disease (Lourenco et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences have also been found in work examining exercise effects [48]. Females have been shown to benefit more from exercise experiences compared to males [49].…”
Section: Plos Onementioning
confidence: 94%
“…One aspect to consider in treadmill studies is that rodents are forced to run while restrained in small running lanes, which may cause stress or anxiety. Furthermore, many of the treadmill protocols use electrical or mechanical stimuli to motivate the animal to continue to run [66,[69][70][71], which induces a stress response. It has been shown that the levels of corticosterone are higher in mice undergoing treadmill exercise with shock stimulations compared to sedentary mice [72].…”
Section: Exercise Regimens Used In Preclinical Researchmentioning
confidence: 99%